Polymyxin B/Tigecycline Combination vs. Polymyxin B or Tigecycline Alone for the Treatment of Hospital-Acquired Pneumonia Caused by Carbapenem-Resistant Enterobacteriaceae or Carbapenem-Resistant Acinetobacter baumannii - Chang, Kang; Wang, Haibo; Zhao, Jianping; Yang, Xianghong; Wu, Bo; Sun, Wenkui; Huang, Man; Cheng, Zhenshun; Chen, Hong; Song, Yuanlin; Chen, Ping; Chen, Xiangqi; et al. (Frontiers in Medicine, 2022)
Introduction: It is not clear whether polymyxin B/tigecycline (PMB/TGC) combination is better than PMB or TGC alone in the treatment of hospital-acquired pneumonia (HAP) caused by carbapenem-resistant organisms (CROs). Methods: We conducted a multicenter, retrospective cohort study in patients with HAP caused by CROs. The primary outcome was 28-day mortality, and the secondary outcomes included clinical success and the incidence of acute kidney injury (AKI). Multivariate Cox regression analysis was performed to examine the relationship between antimicrobial treatments and 28-day mortality by adjusting other potential confounding factors. Results: A total of 364 eligible patients were included in the final analysis, including 99 in PMB group, 173 in TGC group, and 92 in PMB/TGC combination group. The 28-day mortality rate was 28.3% (28/99) in PMB group, 39.3% (68/173) in TGC group, and 48.9% (45/92) in PMB/TGC combination group (P = .014). The multivariate Cox regression model showed that there was a statistically significant lower risk of 28-day mortality among participants in PMB group compared with PMB/TGC combination group (hazard ratio 0.50, 95% CI 0.31-0.81, P = .004), and that participants in TGC group had lower risk of 28-day mortality than PMB/TGC combination group but without statistical significance. The incidence of AKI in PMB group (52.5%) and PMB/TGC combination group (53.3%) was significantly higher than that in TGC group (33.5%, P = .001). Conclusions: The appropriate PMB/TGC combination was not superior than appropriate PMB therapy in the treatment of HAP caused by CRE/CRAB in terms of 28-day mortality.